Project Managers’ Preferences Toward Attributes of Project Management Software Used in the Construction Industry - Linge, Ashish A.; Bihare, Nikesh P.; Kakde, Baldeo B. (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : This study aimed to understand the project managers’ preferences for attributes of project management software used in the construction sector and to evaluate the relative importance of the attributes of project management software considered by project managers. Design/Methodology/Approach : The study used five attributes of project management software, viz., features, number of users, price, license renewals, and data security. The conjoint analysis method was used to understand which of these attributes are the most and least important to project managers. A total of 164 project managers were surveyed by using snowball and purposive sampling techniques. The orthogonal design was used to generate 25 conjoint cards. Findings : The results showed that the attributes of project management software were significantly different from each other. The results revealed that “data security” had the highest utility score, followed by “license renewal,” “price,” “no. of users,” and “features of software.” Practical Implications : The professionals working in the construction industry would benefit from the findings of this investigation. The results will help them to make decisions on the features to be considered while purchasing a Project Management Information System (PMIS). It will help the project management professionals understand the major attributes offered by various PM software, which will eventually help them select the appropriate software as per their requirements. Originality Value : Most of these studies on this topic are conducted in developed countries. However, very few studies have been conducted in India.